1991
DOI: 10.1159/000163663
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nitric Oxide Production by Stimulated Rat Kupffer Cells

Abstract: Macrophages have been described to release nitric oxide (NO) as a cytotoxic radical. This highly unstable substance is as well known as endothelium-derived relaxing factor produced by vascular endothelial cells. Because of its cytotoxic activity the synthesis of NO by rat Kupffer cells, the liver macrophages, upon stimulation with endotoxin (lipopolysaccharide; LPS) and tumor necrosis factor-α (TNF-α) in combination with prostaglandin E2 (PGE2) and dibutyryl cAMP (dBcAMP) was studied. Kup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 1 publication
(1 reference statement)
0
22
0
3
Order By: Relevance
“…Specific inhibition of iNOS activity in vascular tissues requires a better understanding of the factors governing the expression and function of this enzyme. Some progress has been made in elucidating factors regulating iNOS activity in endothelial, macrophage and neuronal cell lines (Nakane et al, 1991;Brune & Lapetina, 1991;Gaillard et al, 1991;Bredt et al, 1992;Severn et al, 1992;Marotta et al, 1992;Hortelano et al, 1992;1993;Feinstein et al, 1993). One factor that appears to play a role in regulating NO production is adenosine 3':5'-cyclic monophosphate (cyclic AMP) but the effect of increasing cyclic AMP levels appears to differ in different tissues such that it is not possible to extrapolate from these studies to VSM cells.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Specific inhibition of iNOS activity in vascular tissues requires a better understanding of the factors governing the expression and function of this enzyme. Some progress has been made in elucidating factors regulating iNOS activity in endothelial, macrophage and neuronal cell lines (Nakane et al, 1991;Brune & Lapetina, 1991;Gaillard et al, 1991;Bredt et al, 1992;Severn et al, 1992;Marotta et al, 1992;Hortelano et al, 1992;1993;Feinstein et al, 1993). One factor that appears to play a role in regulating NO production is adenosine 3':5'-cyclic monophosphate (cyclic AMP) but the effect of increasing cyclic AMP levels appears to differ in different tissues such that it is not possible to extrapolate from these studies to VSM cells.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…This is accompanied by the release of inflammatory cytokines [34,35] and the infiltration of circulating monocytes and neutrophils [36]. Inducible NO synthase (iNOS) is an isoform of NOS expressed under the influence of stimulation by cytokines or microbial products.…”
Section: Discussionmentioning
confidence: 99%
“…A pivotal role for IFN- in the clearance of various intracellular pathogens has been amply demonstrated [53,54] . It has been described that macrophages release the cytotoxic radical, NO [55,56] . In vitro studies suggested that NO induces mitochondrial dysfunction in tumor cells followed by membrane barrier dysfunction in the liver sinusoid [57,58] .…”
Section: Kupffer Cellsmentioning
confidence: 99%